2001
DOI: 10.1016/s0735-1097(01)01672-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of brain natriuretic peptide in risk stratification of patients with congestive heart failure

Abstract: Measurement of plasma BNP concentrations might provide a useful and cost-effective screening tool that helps reduce the need and frequency for more expensive cardiac tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
109
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(118 citation statements)
references
References 28 publications
2
109
1
6
Order By: Relevance
“…Several previous studies [6,7,8,9] have shown N-BNP or BNP to be of prognostic significance in patients with CHF, as good as or better than LVEF or peak VO 2 at predicting death or cardiac events. However, in the studies by Gardner et al [6], Zugck et al [8] and Isnard et al [9], the patients had more severe CHF as reflected by a lower peak VO 2 of 11.8 [6], 14.9 [8] and 16.8 ml/kg/min [9] and a lower LVEF of 15 [6], 22 [8] and 29% [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies [6,7,8,9] have shown N-BNP or BNP to be of prognostic significance in patients with CHF, as good as or better than LVEF or peak VO 2 at predicting death or cardiac events. However, in the studies by Gardner et al [6], Zugck et al [8] and Isnard et al [9], the patients had more severe CHF as reflected by a lower peak VO 2 of 11.8 [6], 14.9 [8] and 16.8 ml/kg/min [9] and a lower LVEF of 15 [6], 22 [8] and 29% [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the studies by Gardner et al [6], Zugck et al [8] and Isnard et al [9], the patients had more severe CHF as reflected by a lower peak VO 2 of 11.8 [6], 14.9 [8] and 16.8 ml/kg/min [9] and a lower LVEF of 15 [6], 22 [8] and 29% [9]. Although the study population in the investigation by Koglin et al [7] had a similar LVEF to our cohort (36%), the peak VO 2 was much lower (15 ml/kg/min). Moreover, none of these studies included exercise duration and peak exercise SBP in their multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, plasma BNP provided important prognostic information in patients with chronic HF, independently of the cause of the disease. In comparison to lower levels, high circulating levels of BNP were associated with high incidence of death or attacks of decompensation [24].…”
Section: Discussionmentioning
confidence: 90%
“…Elevated levels of BNP have been shown in patients with CHF of any cause including diastolic dysfunction and valvular disease and correlate with functional class as well as with prognosis [15,16,17,18]. In addition, BNP levels have been shown to correlate with prognosis in patients following acute coronary syndromes [19].…”
Section: Introductionmentioning
confidence: 99%